Basketball without borders? Similarities and differences among continental basketball championships - Ibanez, S. J.; González-Espinosa, S.; Feu, S.; Garcia-Rubio, J. (Revista Internacional de Ciencias del Deporte, 2018)
The analysis of technical-tactical performance indicators is an excellent tool for coaches, because it provides objective information on the actions of players and teams. The aim of this investigation was to study the performance indicators for the last continental basketball championships. Five continental championships played in 2015 were analysed for a total of 213 matches. The variables analysed were: ball possessions, point difference, points scored, one, two and three point throws attempted and scored, total and defensive and offensive rebounds, assists, steals, turnovers, blocks for and against, fouls committed and received, and evaluation. A descriptive analysis and performance profiles were carried out to characterise the sample. A one-way ANOVA and Bonferroni correction were used to identify the differences among championships. A discriminant analysis was performed to identify the performance indicators best characterising each analysed championship. The results show that there are differences among all the championships and all the performance indicators, except in three point throws scored and blocks. A specific play profile has been identified for each championship. The greatest performance profile differences were found between the Eurobasket and the Afrobasket championships, while the championships with the most similar performance indicator profiles were FIBA America and Asia Cup. These findings are useful for coaches when preparing the different possible scenarios depending on the championship and their respective opponent.